A 500 Watts Single Stage Single Switch Soft Switched CCM PFC Flyback Converter with BCM Control - Mannam, Rayudu; Gorantla, Srinivasa Rao; Vangala, Nagesh (International Journal of Engineering and Technology, 2018)
Single stage isolated AC to DC converters find prominence due to simplicity and efficiency in addition to economics. Boundary control Mode BCM Flyback converters are widely used for such applications up to power levels of 200 watts. For higher power levels, average current control mode PFCs are used and two stage conversion is incorporated. In this paper,  a novel technique for building  a single stage PFC with a Continuous Conduction Mode CCM Flyback AC DC converter is proposed  for 500 watts power. A practicalsingle stage converter is built with power factor correction and input output isolation. The unique feature of the new configuration lies in having only one primary MOSFET switch and adapting BCM control in a CCM Flyback configuration and achieving ZVS and ZCS while in CCM operation. Proposed configuration is best suited for battery charger applications. Also, the absence of high voltage bulk capacitor at the mains input adds lot of advantages in terms of eliminating inrush current and saving PCB area. A working model of 130 V Dc output and 4.0A  is built and the test data are presented  depicting the complete soft switching of all power devices and exhibiting the efficiencies in excess of 95%.